Comparison of drug information in package inserts with standard medical textbook of pharmacology - Jain, Amit; Jindal, Amita; Bansal, Nagma; Arora, Hobinder (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Accurate and reliable drug product information is important for the safe and effective use of medicines. But there are variations in the quantity and quality of information mentioned in different drug information sources and a single credible benchmark is lacking. This study was carried out to compare the presentation and completeness of clinical information in package inserts (PIs) marketed by pharmaceutical companies in India with standard medical textbook of pharmacology. Methods: Out of eighty five PIs of different drugs, only 55 were found eligible to be included in this study after applying inclusion and exclusion criteria. These PIs and medical textbook were analysed for quantitative and qualitative drug information and were compared using Chi square test of two proportions. The p value of 0.05 was used as cut off to evaluate statistical significance. Results: Quantitatively medical textbook was significantly better statistically in context of treatment of overdose and references. No statistically significant difference was observed in relation to information related to mechanism of action (MOA) and pharmacokinetics (Pk). After qualitative analysis, medical textbook was significantly better statistically in context of size and readability, references related to adverse drug reactions (ADRs) and indications and pictures. No statistically significant difference was observed in context of dosing interval, frequency of doses and pharmacokinetic parameters. Conclusions: PIs can be used as a reliable source of drug information by health care professionals in addition to other sources like medical textbooks.